Everyday exposure to power frequency magnetic fields and associations with non-specific physical symptoms. (January 2015) - Bolte, John F.B.; Baliatsas, Christos; Eikelboom, Tessa; van Kamp, Irene
Abstract: The aim of this study was to investigate the association between exposure to extremely low frequency magnetic fields (ELF MF), or power frequency fields, and non-specific physical symptoms (NSPS). In a cross-sectional study, personal exposure to ELF MF was measured for 99 adults selected in and around Amsterdam, the Netherlands in 2009–2010. They were scored on 16 NSPS. As a cut-off point for the individual 24-h time weighted average exposure the 80-percentile (0.09 μT) was chosen. As only one man scored "moderately high" on the somatisation scale against nine women, we decided to proceed analyses only with the 48 women. The crude odds ratio (OR) for women was 8.50 (CI 95%: 1.73–46.75), suggesting that for women environmental exposure to ELF MF is associated with an increased score on NSPS. As this is an exploratory cross-sectional study in a relatively small sample, no conclusions regarding causality can be drawn. Highlights: Electric devices generate exposure to extremely low frequency magnetic fields. The median 24-hours' time weighted average (TWA) exposure is 0.05 μT. The 80-percentile TWA exposure is 0.09 μT for both, men and women. Women score higher than men on non-specific physical symptoms (NSPS). Exposure of women above the 80-percentile is associated with increased NSPS score. Abstract : An exploratory cross-sectional study found a mean exposure to extremely low frequency magnetic fields above 0.09 μT is associated with non-specific physical symptoms in women.